8x-8+3ax=2ax-2a

Simple and best practice solution for 8x-8+3ax=2ax-2a equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x-8+3ax=2ax-2a equation:


Simplifying
8x + -8 + 3ax = 2ax + -2a

Reorder the terms:
-8 + 3ax + 8x = 2ax + -2a

Reorder the terms:
-8 + 3ax + 8x = -2a + 2ax

Solving
-8 + 3ax + 8x = -2a + 2ax

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '2a' to each side of the equation.
-8 + 3ax + 2a + 8x = -2a + 2a + 2ax

Reorder the terms:
-8 + 2a + 3ax + 8x = -2a + 2a + 2ax

Combine like terms: -2a + 2a = 0
-8 + 2a + 3ax + 8x = 0 + 2ax
-8 + 2a + 3ax + 8x = 2ax

Add '-2ax' to each side of the equation.
-8 + 2a + 3ax + -2ax + 8x = 2ax + -2ax

Combine like terms: 3ax + -2ax = 1ax
-8 + 2a + 1ax + 8x = 2ax + -2ax

Combine like terms: 2ax + -2ax = 0
-8 + 2a + 1ax + 8x = 0

Add '8' to each side of the equation.
-8 + 2a + 1ax + 8 + 8x = 0 + 8

Reorder the terms:
-8 + 8 + 2a + 1ax + 8x = 0 + 8

Combine like terms: -8 + 8 = 0
0 + 2a + 1ax + 8x = 0 + 8
2a + 1ax + 8x = 0 + 8

Combine like terms: 0 + 8 = 8
2a + 1ax + 8x = 8

Add '-8x' to each side of the equation.
2a + 1ax + 8x + -8x = 8 + -8x

Combine like terms: 8x + -8x = 0
2a + 1ax + 0 = 8 + -8x
2a + 1ax = 8 + -8x

Reorder the terms:
-8 + 2a + 1ax + 8x = 8 + -8x + -8 + 8x

Reorder the terms:
-8 + 2a + 1ax + 8x = 8 + -8 + -8x + 8x

Combine like terms: 8 + -8 = 0
-8 + 2a + 1ax + 8x = 0 + -8x + 8x
-8 + 2a + 1ax + 8x = -8x + 8x

Combine like terms: -8x + 8x = 0
-8 + 2a + 1ax + 8x = 0

The solution to this equation could not be determined.

See similar equations:

| 3u+12=-7u-18 | | 4(a+1)+1= | | 16a-16-12a-3=75 | | e*8=9*5 | | 5w-7+9=-7 | | -67+6x=1 | | 2x+17=-16 | | 4*3x=19 | | 3k-1=7k+1 | | 2x+1=26 | | F(3)=3*3 | | 0.54=log(x) | | s+4=-7 | | 1/4p-12=60 | | 9f+6f= | | 1/4p-12=12 | | F(2)=3*2 | | 1/4p-12=48 | | -4(2-f)=-16 | | 1/4=p-12 | | 4(x-2)+8x=4(3x+5)-9 | | 5x+4=-15 | | F(3)=2(3-1)+3 | | 18+3x=x-16 | | 8w-2=-12w+-6 | | sinx=0.3188 | | 4(2z+7)=7(z+4)+z | | 0.8x+0.3(150-x)=60 | | F(2)=2(2-1)+3 | | x-9y=-22 | | -9(3-5k)= | | 4+8x-1=4x+45-2x |

Equations solver categories